Traditional Fintech Software Supply Chain Management Design Management Accounting System - Hertati, Lesi; Suharman, Harry; Umar, Haryono (Jurnal ASET (Akuntansi Riset), 2025)
This study aims to determine the emergence of traditional online fintech financial transactions in the supply chain management accounting system of financial reporting in Indonesia. The data used is primary data from the Jakarta regional police who were victims of online loans. The results of the study prove that online loans have an impact on the lower classes. The research data were analyzed using the Structural Equation Model, the target population was 200 people, but 120 people responded. Fintech Online Loans have an impact on the Management Accounting Information System, namely financial and non-financial information through online technology software. The management accounting system has an impact on traditional financial institutions due to economic pressures. The implication of this study is that fintech breakthroughs in the financial sector have caused the fintech application business to be highly sought after by the wider community, which has an impact on the emergence of illegal fintech applications. Previous research used data from P2P countries in the ASEAN region, this study uses primary data in the form of public complaints from police officers who were victims of fintech fraud.